Decomposition of Product Path Graphs Into Graceful Graphs - et. al., P.M.Sudha, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
A decomposition of is a collection such that are edge disjoint and every edge in belongs to. If each is a graceful graph, then is called a graceful decomposition of. The minimum cardinality of a graceful decomposition of is called the graceful decomposition number of and it is denoted by In this paper, we define graceful decomposition and graceful decomposition number of a graphs. Also, some bounds of in product graphs like Cartesian product, composition etc. are investigated.